Parasitic plant causes an ephemeral "rainbow" pattern in a reservoir bank. (11th September 2020) - Bonanomi, Giuliano; Salvatori, Nicole; Zotti, Maurizio; Stinca, Adriano; Motti, Riccardo; Idbella, Mohamed; Cartenì, Fabrizio; Mazzoleni, Stefano; Giannino, Francesco
Abstract: Question: In the fall 2018 we observed an atypical pattern with concentric belts of green, yellow, and brown vegetation. What are the causes of the pattern? Localized water depletion, soil spatial heterogeneity and the activity of pathogenic organisms were tested as alternative hypotheses. Location: Banks of a water reservoir, Alento basin in south Italy (40°19′04.50″ N; 15°06′45.35″ E). Methods: Belts were monitored for floristic composition and plant health status. In each zone, 17 soil parameters were analysed (soil texture, pH, electrical conductivity, limestone content, organic C, Olsen P, total N, C/N ratio, cations exchange capacity, Ca 2+, Mg 2+, Na +, K +, Fe, Cu, Zn, Mn). Soil moisture was monitored by soil probes, positioned at 10 cm depth. The incidence of pathogens and parasitic plants was visually estimated. Finally, model simulations were carried out to explore the interactions between biotic and abiotic factors in the formation of the belts. Results: The vegetation survey revealed that the green belt was characterized by a monospecific stand of Xanthium italicum with a plant density >190 individuals per m 2 . All plants were healthy. In the yellow belt, instead, Xanthium italicum was attacked by the parasitic plant Cuscuta campestris with an incidence >70%. In the brown belt all Xanthium italicum was still standing but dead, with an incidence of Cuscuta campestris attack >94%. No differences in soil chemistry were recorded in the three belts, while soil moisture was slightly lower in the green belt, likely as a result of a higher evapotranspiration rate. The modelling simulation well reproduced the banded vegetation, supporting the role of the parasitic plant in the formation of the pattern. Conclusions: By combining extensive field measurements with detailed modelling work, we revealed, for the first time, the primary role of a parasitic plant in the formation of a regular and ephemeral vegetation pattern. Abstract : We observed an atypical pattern with concentric belts of vegetation along the banks of a water reservoir. Different hypotheses were tested (localized water depletion, soil spatial heterogeneity and the activity of pathogens) combining field work and modelling simulations. The study reveals the primary role of a parasitic plant in the formation of a regular and ephemeral vegetation pattern.